2005
DOI: 10.2135/cropsci2003-714
|View full text |Cite
|
Sign up to set email alerts
|

Planting Systems on Lodging Behavior, Yield Components, and Yield of Irrigated Spring Bread Wheat

Abstract: Stapper, 1987) and in India (Narang et al., 1994). Crook and Ennos (1995) found that stem strength decreased Lodging control of irrigated spring wheat (Triticum aestivum L.) by 20% as N fertilizer rate increased from 160 to 240 kg through both crop management practices and cultivar improvement is needed to increase yield and grain quality in farmer fields, especially ha Ϫ1 . Similarly, application of N at 200 kg ha Ϫ1 decreased in developing countries where wheat production under irrigation pre-breaking str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 7 publications
2
23
1
1
Order By: Relevance
“…What is also clear, for example from the work of Tripathi et al (2005) at CIANO and from the observations of many, is that short stature is a necessary but insufficient condition for adequate lodging resistance in irrigated low latitude wheat. For a factor that so clearly reduces irrigated wheat yield, or the risk of which constrains management for highest yields, it is remarkable how little we have learned about the physiological basis of genetic variation in lodging resistance ; for example, the fact that CIMMYT lines Attila and Babax are very lodging resistant compared to many equally short, or even shorter, spring wheat varieties that readily lodge.…”
Section: Plant Height Dwarfing Genes and Lodgingmentioning
confidence: 99%
“…What is also clear, for example from the work of Tripathi et al (2005) at CIANO and from the observations of many, is that short stature is a necessary but insufficient condition for adequate lodging resistance in irrigated low latitude wheat. For a factor that so clearly reduces irrigated wheat yield, or the risk of which constrains management for highest yields, it is remarkable how little we have learned about the physiological basis of genetic variation in lodging resistance ; for example, the fact that CIMMYT lines Attila and Babax are very lodging resistant compared to many equally short, or even shorter, spring wheat varieties that readily lodge.…”
Section: Plant Height Dwarfing Genes and Lodgingmentioning
confidence: 99%
“…Berry et al [10] reported that shoot and plant leverage were directly determined by the shoot height at its center of gravity, and the amplitude and frequency of movement (natural frequency) caused by wind gusts and the shoot number per plant. Both stem morphology and chemical characteristics of the lower stem are major determinants of stem strength [11][12][13] , whereas anchorage strength is affected by spread and depth of the root plate and strength of the surrounding soil [3,9] . The Rht dwarfing genes on homeologous group 4 chromosomes indirectly affect lodging-related traits through their pleiotropic effects [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Lodging of irrigated wheat can be controlled through crop management practices and cultivar improvement. Bed planted genotypes resulted over 50% less lodging compared with flat planting (Tripathi et al, 2005). Wheat grown on beds has less lodging effect due to more vigorous stem development and also enables to exploit potential yield (Tripathi et al, 2002(Tripathi et al, , 2005.…”
Section: Temperature Stressmentioning
confidence: 99%
“…Bed planted genotypes resulted over 50% less lodging compared with flat planting (Tripathi et al, 2005). Wheat grown on beds has less lodging effect due to more vigorous stem development and also enables to exploit potential yield (Tripathi et al, 2002(Tripathi et al, , 2005. Lodging was due to high velocity winds in February, March and April (71, 69 and 72 Km/h) coupled with rainfall especially in February and March (143 and 115 mm) at milky stage of the crop.…”
Section: Temperature Stressmentioning
confidence: 99%